Perichondritis: inspect the lobule - Eli Bress; Jason E. Cohn (International Journal of Emergency Medicine, 2020)
Abstract Case presentation This is a brief report of a 57-year-old Caucasian female presented with a 4-day history of worsening left ear pain. Her symptoms began with left otalgia and otorrhea which progressed to helical erythema, prompting a visit to the emergency department. She was noted to have erythema of the left auricle and swelling of the left auditory meatus. Our otolaryngology service observed erythema of the auricle with sparing of the lobule. Diagnosis The diagnosis to be otitis externa with perichondritis was established, and we recommended otic ciprofloxacin-hydrocortisone, IV vancomycin, and ciprofloxacin. The patient had marked improvement and was discharged on an oral and otic fluoroquinolone. In this case, the diagnosis of perichondritis was made by a classic physical examination finding: erythema and edema with sparing of the fatty lobule. This key finding helps to distinguish perichondritis from otitis externa.